MANAJEMEN TATA RUANG YANG OPTIMAL DENGAN MEMPERHATIKAN KINERJA JALAN A. YANI KM. 33 s.d. KM. 41 - Mohammad Riza Dauly (Lambung Mangkurat University Press, 2019)
Martapura City and Banjarbaru City are two poles of growth that are experiencing rapid development in the South Kalimantan Province. These two cities are also part of the Banjar Bakula Metropolitan Area. Rapid development, resulting in the transportation sector, has an important and strategic position. This development led to a decrease in the level of road services. The decrease in the level of road network services is indicated by, among others, a reduction in the speed of vehicle operation, congestion in areas of travel attraction. These problems cause many roads that operate with much lower capacity compared to their capacity, so it is necessary to find an optimal solution in the development of transportation infrastructure by analyzing the economical components of road infrastructure development and paying attention to the function of zones along the Jalan Jend Corridor. A. Yani Km.33 to d. Km 41. The study was conducted by analyzing the spatial plan, the existing conditions of traffic performance on the Jalan A. Yani network, Martapura City, and Banjarbaru City. Then scoring analysis of alternative transportation infrastructure development can improve the performance of Jalan A. Yani. The next stage is an economic analysis that takes into account components such as Time Value, BOK, estimated construction cost components, NPV, and BCR in order to obtain optimal transportation infrastructure development solutions. Based on the results of the study, to improve the performance of the road network on Jalan A. Yani, a solution was chosen in the form of infrastructure development of the Banjarmasin toll road (Sungai Lulut) - Martapura. As for the results of the economic analysis found, each was an NPV of - Rp. 3,406,043,000,000.00; BCR of 0.001.